'For I have fed on foreign bread': Modernism, Colonial Education and Fijian Literature. Issue 3 (August 2020) - Long, Maebh; Hayward, Matthew
Abstract : This article examines the ways in which the Fijian authors Vanessa Griffen, Pio Manoa, and Subramani revised and reworked modernist texts in their construction of a local postcolonial literature. These writers were schooled in a colonial education system that was, by the 1950s and 60s, in ideological disarray, as the jingoistic, imperial texts of the English syllabus began to give way to the crisis and self-interrogation of literary modernism. The students who graduated from these classes went on to create a first wave of Fijian creative writing in English. As this article shows, Griffen, Manoa, and Subramani carried into their writing fragments and forms of the texts they had been required to learn by rote, and they refashioned these into new wholes. In their short stories and poems of the late 1960s and early 70s, these writers turned the literature of past imperial breakdown towards present and future needs, adapting fragmentary, perspectival and multivocal texts towards a postcolonial independence still riven by colonially introduced problems. Ultimately, we argue, the creation of this new literature denotes the failure of the education system to impress British superiority upon its colonial subjects, and the success of the subaltern in reclaiming the means of expression.